Bacteriophage Lambda; Abortive Infection of Bacteria Lysogenic for Phage P2 - Lindahl, Gunnar (1970)
The efficiency of plating of wild-type λ on a host lysogenic for P2 is less than 10(-6), and only a small number of infected cells produce progeny phage. Lambda can adsorb and inject its DNA normally in such cells; the DNA can circularize and is not nicked or degraded, but replication is severely impaired. Mutants of P2, which as prophages no longer interfere with λ, have been isolated and found to be recessive to wild type, implying that P2 prophage codes for a diffusible product involved in λ interference. The P2 gene product responsible for preventing λ growth also kills recombination-deficient bacteria of the recB and recC classes under conditions where P2 does not normally kill the host. Mutants of λ that are resistant to interference are recessive to wild-type λ. Thus λ actively participates in its own interference. The λ-mutants that are resistant to interference are unable to synthesize at least two nonessential proteins. In addition, they are unable to grow on recombination-deficient bacteria of the recA class, but they can grow on recA recB double mutants.